Glycemic and Insulinemic Response to Two Doses of Resistant Starch Type 4: A Randomized Controlled Crossover Trial. (29th May 2020) - Steele, Trevor; Maningat, Clodualdo; Seib, Paul; Haub, Mark; Rosenkranz, Sara
Abstract: Objectives: Resistant starches (RS) have beneficial effects on glucose and insulin responses in the postprandial period following carbohydrate (CHO) consumption. In comparison to resistant starch types 1–3, evidence regarding the effects of resistant starch type 4 (RS4) on metabolic responses is sparse. The primary aim of the current study was to determine whether the glycemic and insulinemic responses to a nutritional RS4 bar (RS4) were lower as compared to a puffed wheat bar (PWB), when provided at the standard testing amounts of 50 g available CHO, as well as at a lower dose of 30 g available CHO. Methods: Apparently healthy adults ( n  = 15; 9 M/6F; 26.1 ± 4.8 yrs) participated in this randomized controlled crossover trial. All participants completed six sessions, consuming a dextrose beverage or nutrition bar at each session. Two doses of 50 g and 30 g of available CHO were tested using dextrose control beverages (50DEX; 30DEX), puffed wheat bars (50PWB; 30PWB) and RS4 bars (50RS4; 30RS4). Participants fasted for 10–12 hrs prior to each visit with a minimum 72hr washout between sessions. Whole blood glucose and plasma insulin were measured at baseline and 10, 20, 30, 60, 90, and 120 min post consumption. Primary outcomes were determined using mixed-effects models in GraphPad Prism 8.0.1. Results: Glucose incremental area under the curve (iAUC) was not significantly different between the 50 g conditions ( P  = 0.054). Insulin iAUC was lower for the 50RS4 bar compared to the 50PWB (Mean ± SD; DEX: 3339 ± 2020, PWB: 3968 ± 2454, RS4: 2046 ± 928.7μIU/mL; P  = 0.034), with no differences between 50PWB and 50DEX or 50RS4 and 50DEX (ps > 0.05). Both 30 g bars had lower glucose iAUCs compared to 30DEX (ps < 0.05), with no difference between bars ( P > 0.05). The 30RS4 bar elicited a lower insulin iAUC compared to 30PWB and 30DEX (DEX: 2400 ± 1689, PWB: 1855 ± 665.7, RS4: 1115 ± 832.2 μIU/mL; ps < 0.05) with no difference between 30PWB and 30DEX ( P > 0.05). Conclusions: Resistant starch type 4 elicited a reduced insulinemic response despite a similar glycemic response, at standard testing amounts of 50 g CHO, as compared to puffed wheat. This effect was also observed at the 30 g dose, thereby showing consistent results following consumption. Therefore, RS4 seems to improve insulin function in apparently healthy adults regardless of the amount of RS4 consumed. Funding Sources: MGP Ingredient Inc.